Policy Innovation in the Short Life of State Leadership - Muhadjir Darwin (Populasi, 2021)
Title: Gender Gus Dur: Tonggak Kebijakan Kesetaraan Gender Era Presiden Abdurrahman WahidAuthor: Ashilly AchidstiPublisher: Gading PublishingEdition: First, 2021Number of Pages: 149